Summary of heat flow studies in Nigeria - Akinyemi, Lukman; Zui, Vladimir I. (Journal of the Belarusian State University. Geography and Geology, 2019)
A traditional approach for heat flow determination requires two parameters. They are a geothermal gradient and heat conductivity of rocks comprising the considered depth interval. The geothermal gradient is determined from a thermogram recorded in a wellbore and the heat conductivity is obtained from the laboratory measurements of selected rock samp les. There are some variations of this approach to both get the gradient and heat conductivity values. However, there are many areas without boreholes to register their thermograms, or at least to have several temperature readings at intermediate positions of bottom holes and traditional methods of heat flow determinations cannot be used. Recently another method was proposed to estimate heat flow. It was derived from spectral analysis of magnetic field. During last years it was widely used in Nigeria for areas where deep boreholes are absent. It uses estimates of depths to the base and bottom of the causative body derived from analysis of the magnetic field maps. The base of the causative body corres ponds to the depth of the Curie surface at which rocks lose their magnetic properties. It is known that it happens at the temperature around 580 °C that slightly varies depending on the content of magnetite within the causative body. The temperature at the top of this body is estimated. The heat flow density can be calculated knowing the geothermal gradient within this depth interval and heat conductivity of rocks. A preliminary heat flow density map was compiled based on all accessible heat flow data. A comparison of heat flow data from several regions of the country, determined using both methods provides rather good agreement.
Keywords: geothermics; heat flow; magnetic field; Curie isotherm; Nigeria